2017
DOI: 10.12799/jkachn.2017.28.2.173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Sexual Intercourse and Health Risk Behaviors in Korean and US Adolescents

Abstract: Purpose: Early sexual intercourse is associated with poor health outcomes in adolescents. It is known that sexual intercourse coincides with other health risk behaviors such as smoking, drinking, and using drugs. The purpose of this study is to identify the relationships between sexual intercourse and health risk behaviors among Korean and US adolescents using nationally representative data. Methods: Data were collected from the 2011 Korea Youth Risk Behavior Web-based Survey (29,676 students) and 2011 Youth R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…This study tried to create a conceptual framework based on the ecological system theory, but the intermediate system (family, peer, teacher support) did not fit with this study. Therefore, this researcher finally constructed a conceptual framework based on previous researches including demographic characteristics (7,(9)(10)(11), health behavior characteristics (1,2,13), and mental health characteristics (2,7,12,13,16,17).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study tried to create a conceptual framework based on the ecological system theory, but the intermediate system (family, peer, teacher support) did not fit with this study. Therefore, this researcher finally constructed a conceptual framework based on previous researches including demographic characteristics (7,(9)(10)(11), health behavior characteristics (1,2,13), and mental health characteristics (2,7,12,13,16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents are highly influenced by their friends and are sensitive to social learning, including imitation of their friends' behavior (1). Thus, sociocultural problems, such as alcohol consumption, tobacco use, drug use, and fleeing from home, are reported to be related to sexual intercourse (2,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found an association between early sexual intercourse among high school students and health risk behaviors, including ATOD use behaviors (Louie et al, 2009; Mmari & Sabherwal, 2013; Yeongmi et al, 2017). One specific study assessing the relationship between sexual intercourse and ATOD use among high school students found that students who initiated sexual intercourse early in high school were more likely to smoke, drink alcohol, and use drugs (Ha et al, 2017). Less is known about younger adolescents in middle school.…”
Section: Introductionmentioning
confidence: 99%